A comparison of the soccer talent development systems in England and Canada - Holt, N. L. (European Physical Education Review, 2002)
The purpose of this study was to compare provision for the development of elite soccer players in England and Canada. Data were collected via documentary analysis, fieldwork and formal and informal interviews with Canadian and English youth coaches (N = 12). The respective soccer talent development systems were compared in terms of their normative, institutional, mental states and environmental patterns (Holmes, 1991). Comparative findings showed that the soccer national governing body was responsible for talent development in Canada, whereas professional clubs assumed the primary role in the English system. Canadian coaches possessed more formal education than their English counterparts, but English coaches experienced more inservice coach education than the Canadians. There appeared to be certain discrepancies between the values of coaches and institutional level policies within each of the systems. Suggestions for future research and practice in talent development arising from this cross-cultural comparison are presented.